Differences in ablation size in porcine kidney, liver, and lung after cryoablation using the same ablation protocol - Sompol Permpongkosol (2018)
OBJECTIVE. The purpose of our study was to assess the variation in size of acute necrosis and the variation in thermal map measured during cryoablation in multiple organs using the same ablation protocol for each organ. MATERIAL AND METHODS. Eight female pigs underwent one cryoablation per organ of kidney, lung, and liver performed with open surgery with a 2.4-mm cryoprobe. A 12-and 8-minute double-freeze cycle was used. Intratissue temperatures were monitored using 16-gauge thermometers spaced at 5.0-mm increments from the cryoprobe. The comparison of results among tissues was performed using the multiple analysis of variance. The -20°C thermal diameter was correlated with tissue damage. The kidneys, lungs, and liver were removed and examined histologically for a pathologic complete coagulative necrosis zone. RESULT. A single 2.4-mm cryoprobe had a mean ice ball diameter in kidney, lung, and liver of 38.5 ± 4.7, 35.5 ± 3.6, and 32.5 ± 2.7 mm, respectively. A mean -20°C thermal diameter was achieved at 24.07 ± 1.38 mm in kidney, 12.76 ± 3.0 mm in lung, and 8.8 ± 3.7 mm in liver by means of regression analysis. The acute pathologic complete coagulative necrosis zone size was 21.0 ± 1.56 mm (kidney), 11.6 ± 1.48 mm (lung), and 8.0 ± 1.20 mm (liver). CONCLUSION. The inherent characteristics of different organs manifest different ablation zone sizes during cryoablation despite the same ablation protocol being used. This information should be factored into planning for ablation procedures. © American Roentgen Ray Society.